2009
DOI: 10.1016/j.jtbi.2009.07.039
|View full text |Cite
|
Sign up to set email alerts
|

A new mathematical model for combining growth and energy intake in animals: The case of the growing pig

Abstract: A c c e p t e d m a n u s c r i p tA simultaneous model for analysis of net energy intake and growth curves is presented, viewing the animal's responses as a two-dimensional outcome. The model is derived from four assumptions: 1) the intake is a quadratic function of metabolic weight; 2) the rate of body energy accretion represents the difference between intake and maintenance; 3) the relationship between body weight and body energy is allometric and 4) animal intrinsic variability affects the outcomes so the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…However, Vincek et al (2012) estimated final weights of 233 kg for barrows and 180 kg for gilts, using a sigmoidal function. Literature values of the final live weights indicate differences between breeds (Wellock et al, 2004), sex types and the prediction equations (Strathe et al, 2009). Strathe et al (2009) reported MBW of 406, 471 and 354 kg for barrows, boars and gilts, respectively.…”
Section: Allometric Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Vincek et al (2012) estimated final weights of 233 kg for barrows and 180 kg for gilts, using a sigmoidal function. Literature values of the final live weights indicate differences between breeds (Wellock et al, 2004), sex types and the prediction equations (Strathe et al, 2009). Strathe et al (2009) reported MBW of 406, 471 and 354 kg for barrows, boars and gilts, respectively.…”
Section: Allometric Growthmentioning
confidence: 99%
“…Literature values of the final live weights indicate differences between breeds (Wellock et al, 2004), sex types and the prediction equations (Strathe et al, 2009). Strathe et al (2009) reported MBW of 406, 471 and 354 kg for barrows, boars and gilts, respectively. These estimates are much larger than the present results and the ones previously reported by Knap (2000), which was partly due to the duration of the experimental period.…”
Section: Allometric Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability is due to variation among individuals (related to genetic differences), or to variation of a given process over time for an individual (response to environmental or sanitary issues). The latter approach has been used by Strathe et al (2009) to build a model that includes daily variation in feed intake (DFI) and BW. However, calibration of such a model is complicated, and random processes make it difficult to obtain realistic ranges of parameters (Knap and Schrama, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The porcine population examined contained weaners (piglets up to 10 weeks of age with body weights of approximately 25-30 kg), "human-like" pigs that are often used for surgical experiments (body weight of 45-60 kg), and fatteners (body weights of approximately 110 kg). In future studies, it would be interesting to determine the ontogenetic changes in VSMC orientation and compare those results to the metabolic rate, body mass, and other postnatal (Casas-Carrillo et al 1997;Strathe et al 2009;van Essen et al 2011) or even prenatal (Vallet and Freking 2006;McPherson et al 2004) growth characteristics. Information regarding the changes in SMC distribution during arterial remodeling (Thorne et al 2011;Valentin and Holzapfel 2012), arterial damage due to pressure overload, or angiological intervention by insertion of stents (Weisbecker et al 2012) remains limited.…”
Section: Applicability Of the Results For Further Researchmentioning
confidence: 99%